Ensuring the quality of components produced by metal additive manufacturing using laser generated ultrasound - Everton, Sarah (2018)
Laser powder bed fusion offers many advantages over conventional manufacturing methods, such as the integration of multiple parts which can result in significant weight-savings. The increased design freedom that layer-wise manufacture allows has also been seen to enhance component performance at little or no added cost. However, for such benefits to be realised, the material quality must first be assured.